Data on the genome analysis of the probiotic strain Bacillus subtilis GM5 - Hadieva, G.F. (Data Brief, 2018)
In the present study, we report data on the draft genome sequence of a lipopeptide producing rhizospheric Bacillus subtilis GM5 isolate. The genome consists of 4,271,280 bp with a GC-pair content of 43.3%. A total of 4518 genes including 75 tRNA genes, 3 operons coding for rRNA genes and 56 pseudogenes were annotated. Gene clusters responsible for the biosynthesis of secondary metabolites were validated. Six of the thirty-three clusters identified in the genome code for antimicrobial non-ribosomal peptides synthesis. The Whole Genome Shotgun project of B. subtilis GM5 has been deposited in the NCBI database under the accession number NZ_NKJH00000000 (https://www.ncbi.nlm.nih.gov/nuccore/NZ_NKJH00000000.1).